Percepciones en el Uso del Aplicativo Móvil para el Aprendizaje de Ecuaciones Diferenciales en Estudiantes de Ingeniería. - Olga Lucy Rincón Leal; Mawency Vergel Ortega; Zulmary Carolina Nieto Sanchez (Mundo Fesc)
Higher education faces a significant challenge and an important opportunity by updating its curriculum and creating digital tools that drive and improve learning processes and outcomes. This entails shifting the educational approach from passive students to active students, who generate knowledge through active interaction with instructors. The study of differential equations is fundamental to the training of engineering students. However, learning this subject often represents a significant challenge due to its abstract and complex nature. In this context, there is a need to explore innovative strategies that facilitate conceptual understanding and skill development in this field. The main objective of this research was to understand the learning processes of differential equations in university students. Specifically, it sought to identify learning styles and students' perceptions of this subject, describe the dimensions present in their learning process, and analyze the effectiveness of teaching tools, such as a mobile application, to improve conceptual understanding . To achieve these objectives, a mixed-method methodology with an explanatory scope and a quasi-experimental design was employed . The sample consisted of 28 Differential Equations students, with an average age of 20. Data were collected through surveys and classroom observations, involving engineering students who used the mobile application as a complementary teaching resource. The findings revealed a diversity of learning styles and perceptions, highlighting the importance of adapting teaching strategies to these individual differences. In addition, important dimensions such as motivation and teaching context must be considered . The study also evaluated the effectiveness of teaching tools, such as the Ecuadif mobile application, in improving conceptual understanding . It was found that the use of this application was effective in learning differential equations. It also emphasizes the need to understand students' learning preferences and suggests the implementation of student-centered pedagogical approaches that integrate various tools to improve the learning process.